BS EN IEC 62841-2-23 AMD AA. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 2-23. Particular requirements for hand-held die grinders and small rotary tools (4th February 2022) - British Standards Institution
No abstract available